2021
DOI: 10.1002/jat.4158
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus flame‐retardant tris(1‐chloro‐2‐propyl)phosphate is genotoxic and apoptotic inducer in human umbilical vein endothelial cells

Abstract: Tris(1‐chloro‐2‐propyl)phosphate (TCPP) is a chlorinated organophosphorus flame retardant (OPFR) widely used in consumer goods after the phaseout of brominated flame retardants (BFRs). TCPP can percolate into the indoor and outdoor dusts, leading to its detection in the human body fluids (urine, breast milk) and placenta. However, TCPP has not been studied so far for its toxicity in the human vascular system. Hence, we have used human umbilical vein endothelial cells (HUVECs) and exposed them to TCPP ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…These results were consistent with some experimental results [26] that indicated that renal cell viability was negatively correlated with the concentration of TCPP. One study found that low concentrations of TCPP had pro-apoptotic and pro-activating effects on venous endothelial cells [27], but another study did not detect a significant increase in the rate of apoptosis and ROS in TCPPtreated hepatocytes [28], suggesting that the toxic effects of OPs are somewhat tissue/cell specific. ROS production is usually caused by a change in mitochondrial permeability [29].…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with some experimental results [26] that indicated that renal cell viability was negatively correlated with the concentration of TCPP. One study found that low concentrations of TCPP had pro-apoptotic and pro-activating effects on venous endothelial cells [27], but another study did not detect a significant increase in the rate of apoptosis and ROS in TCPPtreated hepatocytes [28], suggesting that the toxic effects of OPs are somewhat tissue/cell specific. ROS production is usually caused by a change in mitochondrial permeability [29].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells (ECs) release angiocrine factors, which include vascular endothelial growth factors (VEGFs) and fibroblast growth factors (FGFs), to promote and regulate bone growth ( Hu and Olsen, 2016 ; Kaigler et al, 2003 ; Ramasamy et al, 2016 ; Owen-Woods and Kusumbe, 2022 ). Limited studies exist on the ability of FRs to impact EC function, although BFRs and OPFRs have been shown to induce apoptosis and genotoxicity in human umbilical vein ECs ( Chen et al, 2020 ; Saquib et al, 2021 ). Deletion of bone-derived VEGF in osteoblasts obtained from male mice produced immature mineral precursors in culture, whereas it produced mature mineral precursors from female-derived osteoblasts, suggesting a role of VEGF in influencing the skeletal matrix independent of sex hormones in a sex-specific manner ( Goring et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%